2018
DOI: 10.1016/j.jpeds.2018.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Positive Child Health among Individuals Born Extremely Preterm

Abstract: Positive child health assessed using a quantitative PCHI was associated with QoL across the ELGAN cohort at school age. In the current study, the PCHI encompassed 11 outcomes assessed in ELGANs. Future research could include an enhanced panel of child health outcomes to support the use of PCHI as an indicator of positive child health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Eleven adverse outcomes were assessed at the 10-year follow-up: moderate/severe cognitive impairment (7), bilateral blindness (12), hearing impairment (12), gross motor function (GMF) impairment (7); epilepsy (5); attention-deficit/hyperactivity disorder (ADHD) (13); autism (4); anxiety; depression; asthma; and obesity (i.e., body mass index (BMI) above the 95 percentile). Based on these 11 adverse outcomes, a PCHI was generated for each child (8). Supplemental Table S1 compares the maternal and newborn characteristics of the 889 children who were assessed and the 77 children who were not assessed from among the 966 children eligible for study participation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven adverse outcomes were assessed at the 10-year follow-up: moderate/severe cognitive impairment (7), bilateral blindness (12), hearing impairment (12), gross motor function (GMF) impairment (7); epilepsy (5); attention-deficit/hyperactivity disorder (ADHD) (13); autism (4); anxiety; depression; asthma; and obesity (i.e., body mass index (BMI) above the 95 percentile). Based on these 11 adverse outcomes, a PCHI was generated for each child (8). Supplemental Table S1 compares the maternal and newborn characteristics of the 889 children who were assessed and the 77 children who were not assessed from among the 966 children eligible for study participation.…”
Section: Methodsmentioning
confidence: 99%
“…For example, at ten years of age, in the Extremely Low Gestational Age Newborn (ELGAN) study cohort of children born at less than 28 weeks gestation in the United States, 25% had moderate-to-severe cognitive impairment (3), 7.1% had autism spectrum disorder (4), 7.6% had epilepsy (5), 11.4% had cerebral palsy (6) and 4.9% had severe motor impairment (7). We recently described a positive child health index (PCHI) based on 11 adverse outcomes and found that within the ELGAN cohort, higher values on this index were associated with higher Quality of Life (QoL) scores (8). Notably, 32% of the cohort had none of the 11 adverse outcomes (PCHI of 100%) at age 10.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals born preterm also experience a higher risk of health disorders (e.g., asthma) and have a shorter life expectancy [ 8 ]. Our team has investigated 11 health disorders that are associated with preterm birth including bilateral blindness, hearing impairment, moderate/severe cognitive impairment, epilepsy, gross motor function impairment, attention-deficit/hyperactivity disorder, anxiety, depression, asthma, autism, and obesity (i.e., body mass index above the 95 percentile) [ 9 ]. Further, preterm birth in the U.S. is associated with billions of dollars of annual societal economic burden [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a first step toward addressing limitations of measures of child health, Bangma et al 2 shows that the positive child health index (PCHI) is correlated with the Pediatric Quality of Life Inventory (PedsQL), which includes measures of quality of life across physical and psychosocial domains as reported by a parent or guardian. The developed PCHI aims to make a connection on the state of well-being of the child beyond the perception of a parent or guardian.…”
mentioning
confidence: 99%
“…Once determined to be associated with the PedQL, the strength of Bangma et al 2 was the development of a PCHI measure that utilizes disease susceptibility or health to further interrogate aspects of positive child health. There are, however, aspects of positive health that can only be ascertained from the individual directly.…”
mentioning
confidence: 99%